Ontology of Iranian-French Cultural Relations: With an Emphasis on Contemporary Iranian History Prior to the Islamic Revolution - Pourarian, Foad; Badr, Payam Nikpour (Journal of History Culture and Art Research, 2017)
Culture is one of the most prominent concepts that can also be the source of many changes in the range of action and application, in addition to its theoretical competence. One of the major outcomes of culture in contemporary history is its importance in international relations, insofar as these relations can broaden the level of relations or even create deep political or economic links between countries. In contemporary history, Iran began its experience of cultural relations with the West, especially France; Reza Shah, who put Iran's modernization at the top of his goals, pursued literacy and expanded academic circles, and in this regard, one of the most prominent of his plans was to send students to the West, especially to France, which also contributed to the expansion of the presence of French culture and language in Iran. The second Pahlavi era was accompanied by a change in some of the transboundary equations, including the emergence of the United States as a superpower, a special interest of Mohammad Reza Shah in the United States as well as Washington's agenda for the presence in Iran that slowly diminished French cultural influence in Iran, and the English language and culture were replaced. However, French ideas and thoughts still constituted a significant part of the educated layers of Iran given its strong presence in the Iranian academic circles in the past.